2007
DOI: 10.1111/j.1467-9280.2007.01984.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Costs of Exposure to Racial Prejudice

Abstract: This study examined how encountering racial prejudice affects cognitive functioning. We assessed performance on the Stroop task after subjects reviewed job files that suggested an evaluator had made nonprejudiced, ambiguously prejudiced, or blatantly prejudiced hiring recommendations. The cognitive impact of exposure to ambiguous versus blatant cues to prejudice depended on subjects' racial group. Black subjects experienced the greatest impairment when they saw ambiguous evidence of prejudice, whereas White su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
190
3
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(208 citation statements)
references
References 21 publications
7
190
3
2
Order By: Relevance
“…Whereas past research on subtle discrimination-and discrimination more generally-has traditionally focused on discrimination as a cause-and-effect process (i.e., discrimination occurs, and these are its consequences; Salvatore & Shelton, 2007), we contend this view of discrimination is oversimplified and insufficient to building a holistic understanding of the underlying processes involved in subtle discrimination. We instead conceptualize discrimination as a reciprocal process that develops and changes over time.…”
Section: The Cyclical Nature Of Subtle Discriminationmentioning
confidence: 84%
“…Whereas past research on subtle discrimination-and discrimination more generally-has traditionally focused on discrimination as a cause-and-effect process (i.e., discrimination occurs, and these are its consequences; Salvatore & Shelton, 2007), we contend this view of discrimination is oversimplified and insufficient to building a holistic understanding of the underlying processes involved in subtle discrimination. We instead conceptualize discrimination as a reciprocal process that develops and changes over time.…”
Section: The Cyclical Nature Of Subtle Discriminationmentioning
confidence: 84%
“…Mikroaggresjon kan skape et fiendtlig klima (Solorzano et al, 2000), svekke studentenes evne til problemløsning (Dovidio, 2001;Salvatore & Shelton, 2007) og vedlikeholde truende stereotypier (Steele, Spencer & Aronson, 2002). Ikke minst kan foreleserens ønske om å unngå Á eller omgå Á problemet ses som et signal om at taushet er en passende respons på slike hendelser eller at det er greit å la nedverdigende bemerkninger passere ubemerket, og dermed implisitt understøtte sexistiske, rasistiske, homofobe eller andre former for undertrykkende handlinger.…”
Section: Sammendragunclassified
“…Ikke desto mindre kan mikroaggresjon skape et fiendtlig laeringsmiljø og svekke studentenes evne til problemløsning, i tillegg til å reprodusere usynlige privilegier som skaper ulike muligheter for ulike grupper i utdanningsinstitusjonen (jf. Dovidio, 2001;Salvatore & Shelton, 2007;Solorzano et al, 2000;Thun & Holter, 2013). Undervisere har derfor et spesielt ansvar i sin pedagogiske virksomhet for å legge til rette laeringssituasjonen slik at etablerte stereotypier og sosiale hierarkier ikke reproduseres.…”
Section: Avslutningunclassified
“…Richeson and Shelton (2003), among others, have shown that the more implicitly biased one is (according to the IAT), the worse one performs in these tests after interracial interactions. This suggests that interracial interactions require self-regulatory efforts that compromise the exercise of similar forms of executive self-control in the Stroop task (see also Salvatore & Shelton, 2007;Sripada, Kessler, & Jonides, 2014). The general suggestion is that the kind of strength of will that is needed to suppress implicit attitudes is often followed by a refractory period.…”
Section: Willpowermentioning
confidence: 99%